An examination of the impact of executive compensation disparity on corporate social performance. (August 2015) - Hart, Timothy A.; David, Parthiban; Shao, Feibo; Fox, Corey J.; Westermann-Behaylo, Michelle
We investigate the relationship between top management team compensation disparity and corporate social performance. We argue that pay structures with high disparity are reflective of transactional, individualistic organizations that foster a shareholder orientation. In contrast, pay structures with low disparity are indicative of relational, cooperative organizations that foster a stakeholder orientation. Examining the effect of these attributes on corporate social performance, we find that corporate social performance is higher in low pay disparity firms than in high pay disparity firms. We discuss our contributions to executive compensation and corporate social performance research and suggest directions for future research.